Immunogenicity and Reactogenicity of a Reduced Schedule of a 4-component Capsular Group B Meningococcal Vaccine: A Randomized Controlled Trial in Infants. (29th April 2020) - Valente Pinto, Marta; O'Connor, Daniel; Galal, Ushma; Clutterbuck, Elizabeth A; Robinson, Hannah; Plested, Emma; Bibi, Sagida; Camara Pellisso, Susana; Hughes, Harri; Kerridge, Simon; Mujadidi, Yama F; Findlow, Helen; et al.
Abstract: Background: The 4-component capsular group B meningococcal vaccine (4CMenB) was licensed as a 4-dose infant schedule but introduced into the United Kingdom as 3 doses at 2, 4, and 12 months of age. We describe the immunogenicity and reactogenicity of the 2 + 1 schedule in infants. Methods: Infants were randomized to receive 4CMenB with routine immunizations (test group) at 2, 4, and 12 months or 4CMenB alone at 6, 8, and 13 months of age (control group). Serum bactericidal antibody (SBA) assay against a serogroup B meningococcal reference strain (44/76-SL), memory B-cell responses to factor H binding protein, Neisseria adhesion protein A, Neisseria heparin binding antigen, Porin A (PorA), and reactogenicity was measured. Results: One hundred eighty-seven infants were randomized (test group: 94; control group: 93). In the test group, 4CMenB induced SBA titers above the putative protective threshold (1:4) after primary and booster doses in 97% of participants. Postbooster, the SBA GMT (72.1; 95% confidence interval [CI], 51.7–100.4) was numerically higher than the serum bactericidal antibody geometric mean titre (SBA GMT) determined post–primary vaccination (48.6; 95% CI, 37.2–63.4). After primary immunizations, memory B-cell responses did not change when compared with baseline controls, but frequencies significantly increased after booster. Higher frequency of local and systemic adverse reactions was associated with 4CMenB. Conclusions: A reduced schedule of 4CMenB was immunogenic and established immunological memory after booster.